Left Ventricular Blood Flow Kinetic Energy Assessment by 4D Flow Cardiovascular Magnetic Resonance: A Systematic Review of the Clinical Relevance - Harjinder Kaur; Hosamadin Assadi; Samer Alabed; Donnie Cameron; Vassilios S. Vassiliou; Jos J. M. Westenberg; Rob van der Geest; Liang Zhong; Amardeep Dastidar; Andrew J. Swift; Pankaj Garg (Journal of Cardiovascular Development and Disease, 2020)
Background: There is an emerging body of evidence that supports the potential clinical value of left ventricular (LV) intracavity blood flow kinetic energy (KE) assessment using four-dimensional flow cardiovascular magnetic resonance imaging (4D flow CMR). The aim of this systematic review is to summarize studies evaluating LV intracavity blood flow KE quantification methods and its potential clinical significance. Methods: A systematic review search was carried out on Medline, Pubmed, EMBASE and CINAHL. Results: Of the 677 articles screened, 16 studies met eligibility. These included six (37%) studies on LV diastolic function, another six (37%) studies on heart failure or cardiomyopathies, three (19%) studies on ischemic heart disease or myocardial infarction and finally, one (6%) study on valvular heart disease, namely, mitral regurgitation. One of the main strengths identified by these studies is high reproducibility of LV blood flow KE hemodynamic assessment (mean coefficient of variability = 6 ±  2%) for the evaluation of LV diastolic function. Conclusions: The evidence gathered in this systematic review suggests that LV blood flow KE has great promise for LV hemodynamic assessment. Studies showed increased diagnostic confidence at no cost of additional time. Results were highly reproducible with low intraobserver variability.